Creating malleable interactive surfaces using liquid displacement sensing - Hilliges, Otmar; Kim, David; Izadi, Shahram (Proceedings of the 3rd IEEE International Workshop on Horizontal Interactive Human Computer Systems (TABLETOP 2008), 2008)
We present a new approach for rapidly prototyping multi-touch and object sensing surfaces. It works by liquid displacement inside a malleable projection surface. The system provides both touch and pressure information and a distinct organic quality when touched. The system is easy to build and produces a clean signal revealing multiple fingers, whole hands and other object outlines that can be processed using computer vision techniques. This approach provides an easy mechanism to build interactive surfaces, requiring no infrared edge lighting or soldering. In this paper we provide an overview of the approach, some of its unique capabilities, and uncover some of the tradeoffs between viscosity of liquid, air pressure, surface malleability and the volume of liquid used. Our aim is to allow practitioners from DIY enthusiasts to researchers to build and experiment with such systems more readily.